Numerical analysis of electrochemically radiative and higher thermally conductive nanomaterials spinning motion due to rotating disk - Latif Ahmad; Umair Khan; Aisha M. Alqahtani; Marouan Kouki; Essam H. Ibrahim; Zuhaib Hamid; Saleem Javed (Scientific Reports)
Abstract Optimization of heat and mass transfer via higher thermally conductive generalized nonlinear materials namely, the Cross fluid is one of the major contributions of this work. This particular work is further analyzed effectively in the presence of linear reactions as well as solar radiation. The flow configuration is assumed with anticlockwise rotation which guarantees more heat transfer as compared to the linear or translator motion of such materials. Specifically, the generalized concept of Brownian motion as well as thermophoretic forces are utilized in the swirling motion of shear rate-dependent viscosity material which plays a significant role in science and industries. However, an enhancement in the conduction is caused by the non-uniform nanoparticle concentration and this is due to the involvement of the thermo diffusion phenomenon. Moreover, the probability of an extra degree of freedom to the heat equation is reduced by the introduction of the radiation which alternately provided a significant contribution to the thermal conductivity maximization. Additionally, the appearance of linear reaction in the concentration equation is a foundation that is based on the first-order apparent kinetics is one of the hydrolysis of the anticancer cisplatin drugs. Mathematical equations are developed and then solved by using one of the modified collocation methods. The time relaxation constant reduced the pressure and enhanced the rotational flow speed. The reduction in pedesis and radiation caused enhancement in the pressure and temperature. As the first-order reaction rate increases, the material concentration decreases, while radiation enhances the heat transfer rate. The Schmidt number effectively reduces the mass flow rate, whereas the reaction rate enhances it. The entire scheme is validated by providing a well-matched comparison.